ACTIVE LEARNING METHODS ON STUDENTS' LEARNING MOTIVATION AT MADRASAH IBTIDAIYAH - Abdul Haq AS; Ratu Bai Rohimah; Asep Abdurrohman (Adisam Publisher, 2024)
Learning motivation is a series of impulses or driving forces that come from within oneself and from outside to carry out learning activities so as to cause changes in the goals desired by the learning subject so that they can be achieved. Motivation to learn is very important because motivation drives us to be diligent or enthusiastic in carrying out the process to immediately achieve the desired goals. Motivation to learn is also one solution to dealing with feelings of laziness, although of course feelings of laziness sometimes still come, motivation to learn will prevent us from continuing to be lulled by that feeling of laziness. Using active learning methods, students are trained to raise their motivation. In the active learning method, students are taught to process the subject matter using their mental abilities independently, developing ideas for searching for keywords from the subject matter, so that it is easier to understand and solve difficulties in learning, and able to apply them in everyday life. The application of theory in learning is supported by a spirit of independence and self-confidence, that they already have knowledge, as a light, in the dark night, a compass in determining the direction of their journey in social life which is much more complex in this era of globalization.